"I'm Not Going to Become No Rapper": Stereotypes as a Context of Ethnic and Racial Identity Development. (July 2013) - Way, Niobe; Hernández, María G.; Rogers, Leoandra Onnie; Hughes, Diane L.
Few studies examine how the macro context shapes ethnic or racial identity development during early adolescence. This analysis draws on interview data from 40 African American, Chinese American, Dominican American, and European American middle school students (6th through 8th grade) to explore how stereotypes inform adolescents' ethnic and racial identities. Findings revealed that stereotypes about race and ethnicity intersected with those about gender, sexuality, social class, and/or nationality and these intersecting stereotypes shaped adolescents' ethnic and racial identities. In addition, adolescents used stereotypes about other ethnic and racial groups as contrasts upon which their own ethnic or racial identities were constructed. Finally, adolescents' narratives were dominated, particularly for the ethnic minority youth during their 8th-grade interviews, by the desire to avoid or resist becoming an ethnic or racial stereotype. Findings underscore the importance of examining stereotypes as a context of identity development, the ways in which stereotypes intersect in the construction of identity, and resistance in the study of identity development.